(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
The FSW process parameters such as tool rotational speed, travel speed, material thickness, play a major role in deciding the weld quality. The aim of this work was to investigate the mechanical properties in order to demonstrate the feasibility of friction stir welding for joining Al 6061 aluminum pipe welding was performed on pipe with different thickness (2 to 4)mm, six rotational speeds (485 to14800) RPM and a traverse speed (4 to 10)mm/min was applied. Response surface methodology was used to predict the Tensile strengths, the percentage of elongation and hardness of friction stir welded 6061 aluminum pipe are compared with measured values. The effect of FSW process parameter on mechanical properties of 6061 aluminum pipe has been analyzed in detail. The result acquired through model suggestion (RSM) has been proved to be successful in terms of the agreement with experimental results.